Atividade de compostos naturais e sintéticos na presença de espécies de Candida - Andrade, Fernanda Almeida (2017)
Infections caused by yeasts of the genus Candida are called candidiasis and are considered opportunistic diseases with characteristics ranging from superficial to disseminate. Candida species may develop defense mechanisms to the major antifungal agents available for clinical use against infections, making it difficult and limiting treatment. Natural products can be a source of bioactive compounds against infectious diseases, such as the Curcuma longa Linn or saffron plant as it is popularly known that it has the compound curcumin. This vegetable is used in large scale by the population as food condiment and as natural medicine against inflammatory diseases and infectious diseases. Laboratory-synthesized compounds have been to interest in medical biotechnology, among which the hydrazone derivatives are associated with antimicrobial including antifungal, antioxidant, antiparasitic, anticonvulsive, analgesic, anti-inflammatory and antitumor activity. The objectives were to determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of curcumin and n-acylhydrazone compounds, and also to verify the time-kill curve of Candida, to quantify ergosterol and to evaluate hemolysis of red blood cells after action of both compounds. Twenty isolates Candida spp. in the broth microdilution test for evaluation of the MIC and MFC of the compounds. The time-kill curve and ergosterol assay were checked after treatment of C. albicans ATCC 28367 with the compounds. To evaluate the cytotoxicity of these compounds sheep red blood cells were used. The compound curcumin showed MIC values between 16 and 256 μg/mL and MFC between 128 and values greater than 512 μg/mL. For the n-acylhydrazone derivative the MIC values ranged from 2 to 128 μg/mL and the MFC variation ranged from 256 to values greater than 512 μg/mL. The compounds showed fungistatic action on the growth kinetics of Candida over 48 hours. The determination of ergosterol after contact with the agents in MIC of 64 μg/mL of curcumin and 16 μg/mL of nacylhydrazone was reduced by 29.56 and 53.57%, respectively. The compounds showed hemolytic activity at concentrations of 512 μg/mL. The results observed in this work show that the curcumin and the n- acylhydrazone derivative have promising antifungal properties.